Local Elections in Authoritarian Regimes: An Elite-Based Theory With Evidence From Russian Mayoral Elections. (April 2016) - Reuter, Ora John; Buckley, Noah; Shubenkova, Alexandra; Garifullina, Guzel
Why do authoritarian regimes permit elections in some settings but not in others? Focusing on the decision to hold subnational elections, we argue that autocrats can use local elections to assuage powerful subnational elites. When subnational elites control significant political resources, such as local political machines, leaders may need to co-opt them to govern cost-effectively. Elections are an effective tool of co-optation because they provide elites with autonomy and the opportunity to cultivate their own power bases. We test this argument by analyzing variation in the decision to hold mayoral elections in Russia's 207 largest cities between 2001 and 2012. Our findings suggest that Russian mayoral elections were more likely to be retained in cities where elected mayors sat atop strong political machines. Our findings also illustrate how subnational elections may actually serve to perpetuate authoritarianism by helping to ensure elite loyalty and putting the resources of powerful elites to work for the regime.